CURRENT STATE OF PEDAGOGICAL WORKERS TRAINING FOR THE APPLICATION OF DIGITAL TECHNOLOGIES IN THE EDUCATIONAL PROCESS (Innovative professional education, 2022)
In order to study the level of development of teachers' competence in the use of digital technologies in the training of future skilled workers, a toolkit package was developed, which contained questionnaires and practical tasks. The evaluation was carried out on the basis of the developed indicators according to four criteria (motivational, cognitive, activity, reflexive). It has been found that most educators are aware of the need to use digital technologies in the teaching of academic disciplines and are able to objectively assess the level of their own preparation for this work. At the same time, almost half of the respondents showed a low level of knowledge and experience in choosing digital technologies in the training of future skilled workers.
Keywords: vocational education; digitalization of education; pedagogical workers; digital technologies; educational process